A SYNTACTICAL STRUCTURE ANALYSIS OF METAPHORS IN THE TRANSLATION OF LAYLA MAJNUN'S ROMANCE IN 2002 - Elita Ulfiana (CMES (Center of Middle Eastern Studies), 2021)
The purpose of this study is to describe the syntactic structure in the metaphors in Layla Majnun's translation of the novel. The data was obtained from the novel Layla Majnun published by Navila through listening with simak bebas libat cakap technique. Data analysis was padan using pilah unsur tertentu method, namely by sorting certain elements using referential sorting. The results showed that the metaphorical structure in Layla Majnun's novel was dominated by phrases and clauses. Images in the structure of phrases and clauses are displayed through the categories of nouns and verbs. The form of the verb in the clause is found in the form of action verbs, events and circumstances. The variety of these forms proves that the metaphorical structure is consistent in constructing its construction to form a concrete meaning that is easily understood by the reader.